Development of Android-Based E-Module Learning Media in an Effort to Improve Grade X Mathematics Learning Outcomes at SMA Pramadina Bogo - Imam Mubarok; Widyasari; Zainal Abidin Arief (International Journal of Instruction and Smart Education, 2023)
This research aims to develop learning media in the form of android-based e-modules in class X mathematics learning at SMA Pramadina. The research was conducted for five months using a 4-D development model consisting of 4 stages, namely Define, Design, Develop, and Disseminate or adapted into a 4-P model, namely defining, designing, developing, and deploying. This study used the validation of 3 experts, namely design, media and material experts and conducted an effectiveness test using the t test. The findings in this study show that the development of android-based e-modules is feasible and effective for use in mathematics learning at the high school grade X level.